The Effects of the Heme Oxygenase-1/Carbon Monoxide System on Cardiorespiratory Control in Fish - Tzaneva, Velislava (Université d'Ottawa / University of Ottawa, 2016)
Endogenously produced carbon monoxide (CO) is an important gaseous signalling molecule which regulates a variety of cardiorespiratory functions. CO is produced in cells by the heme oxygenase (HO) family of proteins by the breakdown of heme into equimolar amounts of CO, bilirubin and Fe2+. My thesis focuses on the hypoxia- and hyperoxia-inducible HO-1/CO system exclusively and aims to provide the first evidence that the HO-1/CO system is involved in cardiorespiratory control in the zebrafish (Danio rerio) and goldfish (Carassius auratus). Overall, I hypothesise that the HO-1/CO system acts as a negative regulator of cardiorespiratory function in fish. Using immunohistochemistry, I was able to characterise the distribution of HO-1 and thus reveal the potential for endogenous CO production (from heme breakdown) in branchial and skin neuroepithelial cells (NECs; putative O2 chemoreceptors) and associated innervation as well as the heart of the developing zebrafish larva. The presence of HO-1 in these structures suggests the likelihood of specific and localized production of CO in fish. To assess the functional significance of the HO-1/CO system in control of cardiorespiratory function, I used pharmacological and gene knock down approaches to diminish HO-1 activity, and presumably endogenous CO production, in adult and larval fish, respectively. The results from these experiments provided evidence that 1) CO has an inhibitory influence on ventilation in goldfish and zebrafish but that its function is temperature- and species-dependent and 2) showed that the HO-1/CO system tonically inhibits cardiac activity in larval zebrafish.
Keywords: ventilation; neuroepithelial cell; gill; heart; pacemaker cell; chemoreception; oxygen; larva; zebrafish; goldfish; heart rate